Linear and decorative displacement in Islamic ceramics (Journal of the College of Basic Education, 2022)
There are many different cognitive concepts and have occupied intellectual propositions, modern sciences, critical approaches and contemporary studies, especially in the twentieth century and at various levels, artistic and academic fields as well as humanity, Whether its field is philosophical, aesthetic, or critical. Among those theories, the displacement theory was one of the modern critical sciences at the aesthetic level, which made fine arts alike an experimental field that tries to explore the vocabulary and institutions of that theory, which began to take in its fields new challenges in front of this huge amount of knowledge and artistic storage of the tremendous diversity that is characterized by In the twentieth century, which began to deal with the study of aesthetic phenomena to find out the merits of those phenomena, which took these institutions to be effective and applied ideas that contribute to the direction of correct steps and an aesthetic path according to the convergence and proximity that this theory launched by showing it and through the application of its institutions overlapping and intertwining many concepts that have An important matter at the beginning of the twentieth century as well as its applications in various fields of arts.